An Empirical Evaluation of the Potential for Including Shareholders in Corporate Constituency Programs - Baysinger, Barry D.; Keim, Gerald D.; Zeithaml, Carl P. (Academy of Management Journal, 1985)
The purpose of this research was to extend the literature related to the effectiveness of corporate political strategies. The research examined the attitudes of 2,151 shareholders from six major corporations to investigate the feasibility and effects of including shareholders in corporate constituency programs. The results suggest that shareholders, most of whom generally support corporate political activity and desire involvement in these efforts, are a resource that firms can employ to influence their external political environments. The results also suggest that constituency building activities have a positive effect on shareholder attitudes.